Direct Torque Controlled Induction Motor Drive - Verma, Abhishek (My University, 2011)
In conventional Direct Torque Control (DTC), the selection of flux linkage and electromagnetic torque errors are made within the respective flux and torque hysteresis bands, in order to obtain fast torque response, low inverter switching frequency and low harmonic losses. However, DTC drives utilizing hysteresis comparators suffer from high torque ripple and variable switching frequency. Space Vector Modulation (SVM) is the strategy to minimize the torque ripple of induction motor in which, the stator flux level is selected in accordance with the efficiency optimized motor performance. SVM method is incorporated with direct torque control (DTC- SVM) for induction motor drives. However, the basis of the DTC-SVM strategy is the calculation of the required voltage space vector to compensate the flux and torque errors exactly by using a predictive technique and then its generation using the SVM at each sample period. In this thesis work, the simulation of different DTC schemes (Conventional DTC and DTC-SVM) has been carried out using MATLAB/SIMULINK and the results are compared.
Keywords: Matlab-Simulink Model; Direct Torque; Induction Motor Drive